Pump Up Your Sales With These Remarkable Sales Responsiveness Marketing On Customer Satisfaction In The Automotive Industry Tactics - Eman Sulaiman; Ronaldi WIjaya (UIN Mataram, 2021)
The purpose of this study was to examine the effect of responsiveness marketing on customer satisfaction in the Automotive Industry. To test these variables, researchers used customers at PT. AUTO2000 Cirebon as the object of research. This type of research is quantitative descriptive. The research was conducted using a survey method by distributing questionnaires to 100 customers. The results of research on responsiveness marketing, showed that it positively significantly affected customer satisfaction that the calculation results obtained t-count > t-table; 2.812 > 0.677. Then H0 is rejected and Ha is accepted, meaning that there is a significant influence between responsiveness marketing on customer satisfaction. R Square of 0.75. This shows that the percentage of the contribution of the independent variable of responsiveness marketing on the dependent variable of customer satisfaction is 75 percent.